Effect the Addition of Biodiesel from Nyamplung Oil (Calophyllum Inophyllum) on Performance and Emission Characteristics of Diesel Engines - Abdul Hamid; Amin Jakfar; Saiful Saiful; Ike Dayi Febriana; Faizatur Rohmah (Jurnal Teknik Kimia dan Lingkungan, 2022)
In this study, the use of biodiesel from nyamplung oil (Calophyllum Inophyllum) was studied through a transesterification reaction using a heterogeneous catalyst of CaO from limestone originating from Pamekasan, Madura. The composition ratio used between nyamplung oil and methanol in the transesterification reaction was 1:12 (mol/mol) with the addition of 4% CaO catalyst. The biodiesel that is formed is then tested for its performance and emission characteristics in diesel engines with various fuel mixtures between pure diesel and biodiesel (B-10, B-20, B-30, B-40, B-100 and S-100). The test results for biodiesel blends with the highest power produced from B-10, B-20, B-30 and B-100 fuels were 0.26 kW each at a load of 250 watts. While at a load of 500 watts, the highest power is obtained from the B-40 fuel, which is 0.58 kW. The results of performance testing using S-100 fuel obtained the highest power values ​​of 0.27 and 0.58 kW, respectively, with a load of 250 and 500 watts. Performance testing for biodiesel blends, the highest torque value was obtained when using B-10, B-20, B-30 and B-100 fuels, which were 1.65 N.m each with a load of 250 watts. While at a load of 500 watts, the highest torque is obtained on B-40 fuel, which is 3.69 N.m. The fuel S-100 produces torque of 1.71 and 3.69 N.m, respectively, with a load of 250 and 500 watts. Emission gases characteristics of carbon monoxide (CO), nitrogen monoxide (NO) and nitrogen oxides (NOx) showed the lowest concentrations obtained in B-100 fuel were 387 ppm, 92 ppm and 96 ppm, respectively. Meanwhile, the highest concentrations of CO, NO and NOx emissions were produced from pure diesel fuel (S-100), namely 574 ppm, 126 ppm and 132 ppm, respectively.